Upaya Meningkatkan Kemampuan Daya Ingat Anak Slow Learner Melalui Metode SCL Bagi Siswa Kelas VIII Putri SMP MIBS Kebumen - Hanafiah Lutfi Hakim; Siti Aisyah Lubis; Siti Fatimah; Benny Kurniawan (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to examine the effectiveness of the Student Center Learning (SCL) method in increasing memory retention in slow learning children. The research media used was class action assessment. The aspects studied included the learning model given by the teacher and its implementation in learning and the learning outcomes of slow learners. This research was conducted at SMP MIBS Kebumen with a sample of 5 slow learner children and 23 normal children. This research method uses qualitative methods. Data collection techniques were carried out by observing and testing through two PTK cycles. To analyze the data using observation sheets of student activities, giving ideas and suggestions, group discussions and expressing opinions. The results obtained from this study are very significant improvements in improving the memory of slow learning students. Based on these results it was concluded that the SCL learning model was applied to help improve slow learner student learning outcomes. Teachers and educators can utilize this strategy to meet the needs of slow learners and enhance their learning experience.